The Risk of Escalating Cyberattacks and Financial Fraud During Wartime: The Maturity of The County's Judicial System in Combating Cyber and Financial Crimes - Hanna Yarovenko; Iryna Pozovna; Roman Bylbas (Financial Markets, Institutions and Risks)
This study assesses the maturity of Ukraine's system for combating cyber and financial crimes under wartime conditions, focusing on the heightened risks caused by escalating cyberattacks and financial fraud during conflict. As adversaries exploit vulnerabilities in Ukraine's digital infrastructure, this research examines the system's preparedness, judicial efficiency, and alignment with international cybersecurity standards. Using data from the General Prosecutor's Office of Ukraine (2014–2024), the study employs quantitative analyses, including maturity index calculations, trend assessments, and lag analysis through statistical modelling. Key offense categories include unauthorized system interference, malicious software distribution, and restricted information dissemination. The results reveal significant fluctuations in the system's maturity over the study period, with periods of heightened judicial efficiency interspersed with notable delays in processing cyber and financial crime cases. Unauthorized system interference incidents increased fourfold over the decade, reaching 440 cases by late 2024, with judicial responses lagging by an average of one quarter for certain crimes. Similarly, crimes involving the dissemination of restricted-access information experienced judicial delays of up to one year. The maturity indices highlight areas of progress, such as improved prosecution rates for specific crimes during peak conflict periods, but also expose systemic inefficiencies in addressing advanced financial fraud and cryptocurrency-related crimes. Dynamic trends underscore the direct impact of hybrid warfare on cybercrime dynamics. The rapid digitalization of financial systems and public services during the war has expanded attack surfaces, with cybercriminals exploiting vulnerabilities in digital banking platforms and cryptocurrency transactions. While judicial efficiency has shown improvement in prosecuting certain offenses, the overall maturity of the system remains inconsistent, reflecting gaps in enforcement and resource allocation. These findings emphasize the need for Ukraine to align its cybersecurity and financial crime prevention frameworks with international best practices, ensuring resilience against evolving threats. This research contributes to the global understanding of cybersecurity challenges in wartime, offering practical insights for policymakers. It highlights the importance of adaptive frameworks and international cooperation in strengthening national resilience. Despite its contributions, the study acknowledges limitations, including reliance on secondary data and the unique geopolitical context of Ukraine, which may limit generalizability. Future research should explore qualitative aspects of institutional capacity and public trust to complement the quantitative findings. Overall, this study provides an evidence-based foundation for enhancing Ukraine's cybersecurity maturity and offers valuable lessons for other nations navigating similar crises.